Pengaruh Penggunaan Celebrity Endorser dan Promotion di Media Sosial Instagram yang di Mediasi Minat Beli Terhadap Keputusan Pembelian (Studi pada Princess Fazion Malang) - Septi Dwi Kurnia Sari; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This study were proposed to determine the effect of CeIebrity Endorser and Promotion which are mediated by buying interest as an intervening variable on purchasing decisions.Population that used in this study was the society of Malang who has made a purchase at Princess Fazion MaIang. Sampling technique is purposive sampling with a total sample of 82 people. And analysis technique is path analysis method. The results show that Celebrity Endorser has no direct effect on purchasing decisions, but Promotion has a positive and significant effect on purchasing decisions. Celebrity Endorser has a positive and significant effect on buying interest, Promotion has a positive and significant effect on buying interest, and buying interest has a positive and significant effect on purchasing decisions. From these results indicate that buying interest can mediate the effect of Celebrity Endorser and Promotion on purchasing decisions. The amount of CeIebrity Endorser's indirect effect on purchasing decisions mediated by buying interest is greater than the amount of Celebrity Endorser's direct effect on purchasing decisions. Meanwhile, the amount of Promotion's direct effect on purchasing decisions is greater than the amount of Promotion's effect on purchasing decisions mediated by buying interest.